The effects of orthodontic tooth movement in endodontically treated teeth (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2019)
There are no relevant contraindications to orthodontic treatment of previously endodontically treated teeth, considering the quality of the obturated teeth, the health of the periodontal membrane, along with careful application of orthodontic force. Although, there is usually some degree of reversible or transient pulpal inflammation  even  in  healthy  teeth  during  orthodontic  treatment,  application  of  light  and  intermittent orthodontic force will reduce the risks provided sufficient time is given to allow proper repair of the dental tissue.  However,  there  may  be  a  few  hazards  associated  with  the  treatment  of  endodontically  involved teeth, some of which mainly include root resorption and ankylosis. This article will show some cases of teeth which had undergone  root canal treatment prior to orthodontic management and further observed whether orthodontic tooth movement had caused any resorption in the root filled teeth.  Root canal treated teeth can be moved orthodontically to the same extent as vital teeth, providing, a controlled force applica- tion to avoid risk of inflammatory root resorption.Ban J Orthod & Dentofac Orthop, April 2017; Vol-7 (1-2), P.12-15